Integrating spirituality into multicultural counseling - Fukuyama, Mary A. (Multicultural aspects of counseling and psychotherapy., 1999)
This is a very helpful book for mental health professionals providing therapy, counselling and health and social care services, as it explores and integrates multicultural and spiritual perspectives in a practical and informative manner. It highlights the fact that spiritual dimension has an enormous relevance to multicultural counselling' - Transcultural Psychiatry This book challenges practitioners with the proposal that integrating spiritual values in multicultural counselling and exploring spirituality from multicultural perspectives are synergistic and mutually reciprocal processes.